Adaptation of organizational citizenship behavior checklist in Indonesia - Pupunden, Manik; Susanto, Hery (Trigin Publisher, 2023)
The Organizational Citizenship Behavior-Checklist was developed by Fox & Spector in 2011, and has undergone multiple adaptations in languages other than English. The study aimed to validate the OCB-C in Indonesia, which had been adapted for this purpose. The validation process employed Confirmatory Factor Analysis and involved 261 employees in Indonesia (n = 261), selected using convenience sampling techniques The Confirmation Factor Analysis was conducted using JASP 16.0 software. The findings of this study indicate that the adapted OCB-C in Indonesia has met the goodness of fit criteria (RMSEA = 0.0048, CFI = 0.0952), and demonstrates reliability with a Cronbach’s alpha coefficient of .902. These results suggest that the adaptation of OCB-C retains its unidimensional nature within the utilized indicators for assessing levels of Organizational Citizenship Behavior.